Aplikasi Mengenal Tarian Tradisonal Indonesia Berbasis Android Menggunakan Algoritma Fisher Yates Shuffle - Marlinda, Linda (Sinkron : jurnal dan penelitian teknik informatika, 2018)
— Unique Culture in Indonesia known by the world with the result that traditional culture, the results of which are traditional culture, in the form of visual art, music, and dance. Since the first until the current culture in Indonesia is growing, and gave birth to new cultures. With cultural diversity in each area and region of the Indonesian nation is a pride for the Indonesian nation with the cultural diversity of society to remain united regardless of differences between traditional budaya.Tari also has a purpose, its own merits, not as one region to another, that the uniqueness of our art. Along with the development of mobile technology, especially the Android operating system are much in demand by the world community. Where the operating system is installed in the mobile and application usage can also be used anywhere and anytime. Researchers wanted to try to analyze the needs that exist for the application of traditional dances information western Java based android